Pedagogical conditions of ethno-pedagogical competence of future teachers - Aubakirova, K.F.; Ishanov, P.Z.; Danek, J.; Аbdrazakova, А.А.; Bolatbekova, A.K.; Bakenova, A.M. (Publ.KarSU, 2017)
In the content of the article, the authors argue that the use of system analysis suggests the following logic for the development of the problem of ethno-pedagogical competence of future teachers: namely, the pedagogical conditions for the formation of ethno-pedagogical competence of future teachers, where it is necessary to define the concept of «ethno-pedagogical competence of the future teacher» as a starting point in elucidating the essence of the phenomenon being studied. By formation we understand the conscious development by the subject of the perfect form of action, as mastering this by the future teacher positively changes not only his activity, but himself. The starting point for identifying the possibilities of the pedagogical process and developing a system of pedagogical conditions for the formation of the ethno-pedagogical competence of future teachers is the definition of the phenomenon being studied, which is defined as the aggregate of integrative professionally significant personal qualities that contribute to the realization of the relevant knowledge, skills, skills and experience of professional activity in a multiethnic educational environment.
Болашақ мұғалімдердің этнопедагогикалық құзыреттілігінің педагогикалық шарттары
Педагогические условия этнопедагогической компетентности будущих учителей
Keywords: education; pedagogical conditions; ethno-pedagogical competence; formation; pedagogical process; pedagogical activity; teacher; professional qualities